The other side of the sky - Kaufman, Amie; Spooner, Meagan (HarperTeen, an imprint of HarperCollins Publishers, 2020)
"Prince North's home is in the sky, in a gleaming city held aloft by intricate engines, powered by technology. Nimh is the living goddess of her people on the Surface, responsible for providing answers, direction--hope. North's and Nimh's lives are entwined--though their hearts can never be. Linked by a terrifying prophecy and caught between duty and fate, they must choose between saving their people or succumbing to the bond that is forbidden between them" --
The first book in a YA duology, prequel to: Beyond the end of the world
Keywords: Princes / Juvenile fiction; Goddesses / Juvenile fiction; Prophecies / Juvenile fiction; Imaginary places / Juvenile fiction; Magic / Juvenile fiction; Fate and fatalism / Juvenile fiction; Survival / Juvenile fiction; Prophecies / Fiction; Love / Fiction; Man-woman relationships / Juvenile fiction; Lieux imaginaires / Romans, nouvelles, etc. pour la jeunesse; Habiletés de survie / Romans, nouvelles, etc. pour la jeunesse; Princes / Romans, nouvelles, etc. pour la jeunesse; Déesses / Romans, nouvelles, etc. pour la jeunesse; Prophéties / Romans, nouvelles, etc. pour la jeunesse; Destin et fatalisme / Romans, nouvelles, etc. pour la jeunesse; Relations entre hommes et femmes / Romans, nouvelles, etc. pour la jeunesse; Histoires d'amour; Young adult fiction; Fantasy fiction; Juvenile works; Young adult works; Science fiction; Jugendbuch